2017
DOI: 10.1103/physrevapplied.7.024024
|View full text |Cite
|
Sign up to set email alerts
|

Species-Independent Femtosecond Localized Electric Field Measurement

Abstract: We present an optical measurement method using a femtosecond laser for non-intrusive measurements of electric field strength and orientation in virtually any gas or gas mixture via second harmonic generation. This simple method takes advantage of the asymmetry in polarizability induced by an applied electric field, which enables the otherwise forbidden second harmonic generation in any centrosymmetric or homogeneous media. The use of a femtosecond laser source permits high intensities without avalanche breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 19 publications
3
100
0
Order By: Relevance
“…Therefore only the results obtained in relatively diffuse plasmas, such as occur in surface ionization waves in same polarity pulses, are representative of the electric field in the ionization front. Measurements of the electric field in well-defined, isolated plasma filaments, generated in alternating polarity pulse trains, would require higher spatial resolution, which can be obtained by using a shorter focal distance lens [18], combined with a suitable signal discrimination technique such as cross-correlation spectroscopy [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore only the results obtained in relatively diffuse plasmas, such as occur in surface ionization waves in same polarity pulses, are representative of the electric field in the ionization front. Measurements of the electric field in well-defined, isolated plasma filaments, generated in alternating polarity pulse trains, would require higher spatial resolution, which can be obtained by using a shorter focal distance lens [18], combined with a suitable signal discrimination technique such as cross-correlation spectroscopy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Development and experimental validation of higher fidelity ns pulse discharge models needs detailed non-intrusive measurements of the electric field in the plasma. Recently, remarkable progress has been made in development of a non-intrusive laser diagnostic technique for electric field measurements in air plasmas, fs/ps second harmonic generation (SHG) [18,19]. This method offers several advantages over the reduced electric field measurements by optical emission spectroscopy (OES) [20,21], including straightforward absolute calibration, measurement of individual components of the electric field vector, and capability of acquiring data over a much larger spatial domain and wider range of time scales, where plasma optical emission is not detected.…”
Section: Introductionmentioning
confidence: 99%
“…Wakefield experiments are being performed at present. We can imagine more experimental challenges, such as adding external magnetic fields and more diagnostics, such as a nonintrusive optical measurement of the local electric field with high spatial and temporal resolution using the non-resonant four-wave mixing interaction with a driving femtosecond pulsed laser beam [58]. Finally, we should mention that we have found that for sufficiently high-power microwaves the plasma electrons can completely be driven to the waveguide walls like a snowplow effect leaving a positively charged plasma (see Figure 13) [57].…”
Section: Discussionmentioning
confidence: 99%
“…Wakefield experiments are being performed at present. We can imagine more experimental challenges, such as adding external magnetic fields and more diagnostics, such as a nonintrusive optical measurement of the local electric field with high spatial and temporal resolution using the non-resonant four-wave mixing interaction with a driving femtosecond pulsed laser beam [58].…”
Section: Discussionmentioning
confidence: 99%
“…SHG. Recently, another nonintrusive laser-diagnostic method for electric-field measurements was demonstrated using SHG by a fs-laser beam passing through an electrostatic electric field in atmospheric air (see figure 7) [65]. This method is based on the asymmetry in polarizability that is induced by an applied electric field that allows the observation of SHG, which is otherwise forbidden in homogeneous media.…”
Section: Spectroscopic Methods For Electric-field Measurementsmentioning
confidence: 99%